Gabapentin, Pregabalin and Vigabatrin Quantification in Human Serum by GC-MS After Hexyl Chloroformate Derivatization - Hložek, Tomáš; Bursová, Miroslava; Coufal, Pavel; Čabala, Radomír (Journal of analytical toxicology, 2016)
A simple, sensitive and robust method for simultaneous determination of antiepileptic drugs (gabapentin, pregabalin and vigabatrin) in human serum using GC-MS was developed and validated for clinical toxicology purposes. This method employs an emerging class of derivatization agents - alkyl chloroformates allowing the efficient and rapid derivatization of both the amino and carboxylic groups of the tested antiepileptic drugs within seconds. The derivatization protocol was optimized using the Design of Experiment statistical methodology, and the entire sample preparation requires less than 5 min. Linear calibration curves were obtained in the concentration range from 0.5 to 50.0 mg/L, with adequate accuracy (97.9-109.3%) and precision (<12.1%). The method was successfully applied to quantification of selected γ-aminobutyric acid analogs in the serum of patients in both therapeutic and toxic concentration ranges.
Keywords: Formates; Pregabalin; Cyclohexanecarboxylic Acids; Amines; lidé; aminy; Vigabatrin; Gas Chromatography-Mass Spectrometry; Calibration; gamma-Aminobutyric Acid; antikonvulziva; Humans; GABA; plynová chromatografie s hmotnostně spektrometrickou detekcí; pregabalin; kyseliny cyklohexankarboxylové; kalibrace; Anticonvulsants; vigabatrin; formiáty; Computer-Aided Design; design s pomocí počítače